2015
DOI: 10.1111/and.12449
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced apoptosis and mechanism of epididymal dysfunction in rats with left-side varicocele

Abstract: To investigate the relationship between hypoxia and epididymal dysfunction and the mechanism of epididymal dysfunction in rats with left-side varicocele, a total of 45 male Wistar rats were randomly divided into three groups in average. The expression of hypoxia-inducible factor-1α (HIF-1α) was detected by Western blot and immunohistochemical analysis respectively. HIF-1α was expressed in the experimental group, and the positive rate was significantly higher than that of either the sham or the control group (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…HIF 1 alpha (HIF‐1α) is a unique marker of tissue hypoxia and is stably expressed in hypoxic tissues (Doedens et al, ). Studies have confirmed a significant increase in the expression of HIF‐1α in the testis and epididymis of patients with varicocele (Zhang et al, ). HIF‐1α expression is increased in hypoxia and binds to the 400 bp hypoxia response element upstream of the promoter of miR‐210‐3p, thereby promoting the expression of miR‐210‐3p.…”
Section: Discussionmentioning
confidence: 82%
“…HIF 1 alpha (HIF‐1α) is a unique marker of tissue hypoxia and is stably expressed in hypoxic tissues (Doedens et al, ). Studies have confirmed a significant increase in the expression of HIF‐1α in the testis and epididymis of patients with varicocele (Zhang et al, ). HIF‐1α expression is increased in hypoxia and binds to the 400 bp hypoxia response element upstream of the promoter of miR‐210‐3p, thereby promoting the expression of miR‐210‐3p.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, Zhang et al . () showed that ELV may cause epididymal hypoxia and dysfunction, and HIF‐1α expression may be useful for predicting germ cell apoptosis in varicocele. In the present study, we showed that HIF‐1α expression was significantly reduced upon varicocelectomy, resulting in the amelioration of hypoxic stress induced by ELV.…”
Section: Discussionmentioning
confidence: 99%
“…Negative controls were processed at the same time. Finally, the AI was calculated by counting the number of positively stained cells/all cells in five randomly selected fields (Zhang et al., ).…”
Section: Methodsmentioning
confidence: 99%